Diversidade e abundância inter-anual no componente herbáceo da caatinga: paralelos entre uma área preservada e uma área antropizada em regeneração natural - SANTOS, Josiene Maria Falcão Fraga dos (2010)
Considering the importance of herbaceous vegetation, the influence of seasonal change on biological diversity and the wide area modified by agricultural activities in caatinga, aimed to characterize the floristic composition and phytosociological structure of the herb community established during the process of natural regeneration in cultivation area abandoned in consecutive years, and identify similarities and differences in biological attributes of the herb community located in a fragment preserved and a anthropized. In Caruaru, Pernambuco, was established 105 plots of 1m2 and within these plots, each individual herb was identified and measured by the height and diameter of the stem / pseudostem at soil level in the years 2008 and 2009. To identify similarities and differences between the fragment preserved and disturbed, was referred to the literature available with information on flora and structure of the herbs in the fragment preserved. In order to determine whether intense disturbance caused byhuman influence on the frequency of life forms, the herbaceous, species were classified according to life form in therophytes, geophytes and chamaephytes. In two years, the herbaceous flora of the area impacted was represented by 86 species, 70 genera and 27 families. Diversity and evenness between years showed no significant differences in contrast and density that varied significantly (albeit with strong variations in total rainfall between years) with 8035 ind.105m-2 and 9284 ind.105m-2 in the first and second years of sampling, respectively. Considering the areas impacted and preserved, 123 herbs were listed and the similarity was low (43%). There was significant difference in diversity, density and evenness among the areas impacted and preserved. Both between years and between areas, the proportion of life-form of the herb has not changed, and the therophytes responsible for the highest percentage in all situations. The differences in the floristic composition and structure of the herbs present in the fragment preserved and habitats, indicate that the time 15 years of natural regeneration on abandoned cropland in the caatinga is not sufficient to recuperate the native flora, with respect to the herbaceous.